2016
DOI: 10.1016/j.pec.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Physician training in self-efficacy enhancing interviewing techniques (SEE IT): Effects on patient psychological health behavior change mediators

Abstract: Objective To explore how physician training in self-efficacy enhancing interviewing techniques (SEE IT) affects patient psychological health behavior change mediators (HBCMs). Methods We analyzed data from 131 patients visiting primary care physicians ≥4 months after the physicians participated in a randomized controlled trial. Experimental arm physicians (N=27) received SEE IT training during three ≤20 minute standardized patient instructor (SPI) visits. Control physicians (N=23) viewed a diabetes medicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 52 publications
0
12
0
1
Order By: Relevance
“…The PCPs (both study arms) will be assessed for their perception of the hassle and the helpfulness of participating in the study, using a modification of a 12-item survey developed by our team for a recent study on a primary care intervention for chronic condition management. 33 The CI-PVP nurse and 5 of the PCPs in the intervention arm will also complete a brief semi-structured interview (10 minutes) on their experiences with the trial and any PVP (either standard PVP or the intervention CI-PVP), as well as their observations on patient reaction to the CI-PVP and discussion of life context during the office visit. All PCPs also will be surveyed for visit difficulty 34 after a single MCC visit prior to the intervention period, 1 and 3 months into the intervention period, and post-intervention period, to ensure CI-PVP does not add to visit burden compared to standard PVP.…”
Section: Discussionmentioning
confidence: 99%
“…The PCPs (both study arms) will be assessed for their perception of the hassle and the helpfulness of participating in the study, using a modification of a 12-item survey developed by our team for a recent study on a primary care intervention for chronic condition management. 33 The CI-PVP nurse and 5 of the PCPs in the intervention arm will also complete a brief semi-structured interview (10 minutes) on their experiences with the trial and any PVP (either standard PVP or the intervention CI-PVP), as well as their observations on patient reaction to the CI-PVP and discussion of life context during the office visit. All PCPs also will be surveyed for visit difficulty 34 after a single MCC visit prior to the intervention period, 1 and 3 months into the intervention period, and post-intervention period, to ensure CI-PVP does not add to visit burden compared to standard PVP.…”
Section: Discussionmentioning
confidence: 99%
“…We found that both SP post-visit ratings and coder ratings of SP visit recordings performed moderately well in detecting physicians who had received training in SEE IT [9, 10], with no significant difference in detection ability between methods. The findings question the need for coder ratings of SP visit recordings to assess physician interviewing behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported the details of our RCT of SEE IT training for PCPs [9, 10]. Briefly, we randomized family physicians and general internists (N=50) from 12 primary care offices in the Sacramento, California area, drawn from the UCD and Sutter health systems.…”
Section: Methodsmentioning
confidence: 99%
“…Although there is this need for training, most of the international studies point to a formative logic still focused on the traditional training and capacities, with measurements of their impacts in the daily work ( 13 - 17 ) .…”
Section: Introductionmentioning
confidence: 99%